Menakar Competitive Strategic Lembaga Perkreditan Desa di Bali - I Gusti Kade Pusdikardiana Alin; Ni Nyoman Sunariani (Jurnal Manajemen dan Bisnis, 2019)
ABSTRACTLembaga Perkreditan Desa (LPD) spread over Bali are one of the financial services managed by Desa Pakraman . The LPD was established with the aim of encouraging the economic development of rural communities with targeted savings and effective capital distribution. Given the increasing number of competitors from other financial institutions, good governance and competitiveness strategies also need to be considered in its development. This study uses qualitative methods aimed at finding out how the competitiveness strategy in the LPD, by collecting data through interviews, observation and documentation. The location of the study was carried out in Negara Subdistrict with two LPDs chosen to represent this study, namely: LPD Desa Pakraman Lelateng (LPD with healthy conditions) and LPD Desa Pakraman Kaliakah Kangin (LPD with unhealthy conditions). Data were analyzed by SWOT analysis. Based on the results of the study it was found that, the LPD of Desa Pakraman Lelateng  had a good image, trustworthiness, competent human resources, good business conditions, problem loans, utilization of technology and operational areas. The strategy that should be implemented is a focus strategy that is to provide services that are maximum for customer trust and an improved risk management strategy. Then in the LPD of Desa Pakraman Kaliakah Kangin, employee loyalty, a bad image of the organization, decreased trust, a decline in business, non-performing loans and perarems that have not been resolved were found. The strategy that should be implemented is a strategy to optimize socialization to the community to restore trust in the institution.